Recontextualização do discurso da ciência da linguagem no livro didático de um curso livre de inglês em Santa Maria-RS - Martini, Andrea (2014)
A contemporary view of the teaching of English as an Additional Language (EAL) implies in recognizing practices of reading as a critical literacy, since the students‟ knowledge of the world need to be articulated so that they can be linked with a perspective that every text can generate plural meanings, revealing, thus, cultural and ideological aspects inherent to any discourse (PENNYCOOK, 1994; CERVETTI, DAMICO and PARDALES, 2000; APPLE, CHRISTIAN-SMITH, 2001). The present study takes part of an umbrella project developed at Laboratório de Pesquisa e Ensino de Leitura e Redação (LABLER). From this on, the general goal of this research is no analyze in what extent a textbook of a private course of EAL in Santa Maria-RS recontextualizes the discourse in the field of Language Science. In order to enable the objective of this study, concepts of language as genre, reading as a critical literacy and learning in the current discourse of Applied Linguistics were investigated. The reading activities must take students into develop analytical competences of contexts of language use so that they can be able to analyze discourses (MOTTA-ROTH, 2006, p. 501) as well as establish connections in order to realize that texts constitute, reconstitute and/or change discursive and social practices (MEURER; MOTTA-ROTH, 2002, p. 12). Cervetti, Pardalles and Damico (2001) propose the concept of critical literary as a way of expanding the concept of critical reading. This view shows reading as a meaning construction process, as a way of knowing the world and as a means of social transformation. In this conception, the teaching institutional objectives must reach the development of the student‟s critical awareness who once was a reader of the world and now turn out to be an actor in the world. The results indicate that the conception of language adopted by the Textbook is, partially, consonant with the interdisciplinary approach about the concept of discursive genre covered by Sociorhetoric, Systemic Functional Linguistics and Critical Discourse Analysis. The conception of reading adopted by the collection touches lightly the assumptions of reading as a critical literacy, but not in a way that highlight the objective of the activities of enabling students to question about the author‟s view, for instance.